A prospective study of iron status in exclusively breastfed term infants up to 6 months of age - Rusia Usha; Faridi MMA; Raj Shashi; Singh Om (BMC, 2008)
Abstract Background Can exclusive breastfeeding until six months of age maintain optimum iron status in term babies? We evaluated iron status of exclusively breastfed term infants in relation to breast milk iron and lactoferrin. Methods In this prospective study in Delhi, India, during the period 2003-2004 normally delivered babies of non-anemic [(Hemoglobin (Hb) = 11 g/dl, n = 68] and anemic (Hb 7 - 10.9 g/dl, n = 61) mothers were followed until 6 months of age. Iron parameters were measured in the cord blood at 14 weeks and 6 months. Breast milk iron and lactoferrin were measured at the same intervals. Results Iron parameters in babies of both groups were within normal limits at birth, 14 weeks and 6 months. Mean breast milk iron and lactoferrin in non-anemic (day 1: 0.89, 6 months: 0.26 mg/l; day 1: 12.02, 6 months: 5.85 mg/ml) and anemic mothers (day 1: 0.86, 6 months: 0.27 mg/l; day 1: 12.91, 6 months: 6.37 mg/ml) were not different on day one or at other times. No relationship was found between breast milk iron, lactoferrin and iron status of the babies. Conclusion Exclusively breastfed infants of non-anemic and anemic mothers did not develop iron deficiency or iron deficiency anemia by six months of age.